2017
DOI: 10.1590/s1413-65382317000300009
|View full text |Cite
|
Sign up to set email alerts
|

Funções Executivas na Dislexia do Desenvolvimento: Revendo Evidências de Pesquisas

Abstract: RESUMO: o objetivo deste artigo é fazer uma revisão sistemática de literatura a fim de analisar produções científicas que abordam as funções executivas (FE) ABSTRACT:The objective of this article is to make a systematic review of literature in order to analyze scientific productions that deal with executive functions (EF) and dyslexia. The method consists on a selection of articles published in the Virtual Health Library (BVS), in the CAPES Periodicals and PUBMED. Were selected 28 papers, 9 from PUBMED, 14 fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 33 publications
0
6
0
2
Order By: Relevance
“…This may happen because, despite the phonological deficits being persistent in dyslexia, there are important differences between this condition, ADHD and intellectual disability. It is observed that, in ADHD and in intellectual disability, there is impairment of other cognitive functions, such as the executive functions 24,25 and reasoning 26,27 , which may have more complex consequences on specific abilities, though this is not necessarily the case in all the children with dyslexia 28 .…”
Section: Discussionmentioning
confidence: 99%
“…This may happen because, despite the phonological deficits being persistent in dyslexia, there are important differences between this condition, ADHD and intellectual disability. It is observed that, in ADHD and in intellectual disability, there is impairment of other cognitive functions, such as the executive functions 24,25 and reasoning 26,27 , which may have more complex consequences on specific abilities, though this is not necessarily the case in all the children with dyslexia 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Given the complexity present in dyslexia, there is no consensus among researchers about the predictive effect of EF in isolation. There is a relegation of some EFs in dyslexics, such as working memory and inhibitory control, but this relegation is not homogeneous in all the individuals surveyed and cannot therefore be pointed out as predictors (Medina, Minetto, & Guimarães, 2017) Few studies addressing intervention in EFs in dyslexics have been found in the literature (Luo, Wang, Wu, Zhu, & Zhang 2013;Lima, Alves, Silva, Azoni, & Ciasca, 2015;Medina et al, 2017). Luo et al (2013) conducted two months of computerized training in working memory in children with dyslexia, which demonstrated improvement in reading skills.…”
mentioning
confidence: 94%
“…However, in a recent systematic literature review, Medina et al (2017) point out that several studies suggest the inclusion of EF stimulation to improve reading performance, considering that multiple dyslexia deficits require broader intervention, not only in phonological MEDINA, G. B. K. & GUIMARÃES, S. R. K. awareness and reading. EF affects "reading strategies involving manipulation of information, response time, the capacity to inhibit distracting stimuli, as well as the alternation between different elements with different meanings" (Medina et al, 2017, p. 450), so the stimulation of EF may also bring benefits to the reading.…”
mentioning
confidence: 99%
“…A Memória de Trabalho (MT) é um sistema cognitivo de armazenamento temporário e limitado, sendo um dos componentes da memória imediata, capaz de reter, manipular e gerenciar temporalmente informações verbais e visuoespaciais, fornecendo suporte aos processos cognitivos e realizando a interface entre a percepção, memória e ação. Esse elemento armazena e retém temporariamente a informação somente durante a execução da tarefa, e assim que a informação não é mais necessária, é descartada logo em seguida (Baddeley, 2002;Lobo et al, 2008;Uehara e Landeira-Fernandez, 2010;Baddeley, 2013;Medina et al, 2017). Baddeley (1983), descreveu que a memória de trabalho está na intersecção entre memória, atenção e percepção.…”
Section: • Memória De Trabalhounclassified
“…O uso das regras de conversão grafema-fonema permite a identificação exata das palavras que possuem correspondência grafia-som regular, entretanto, não identifica palavras irregulares. É durante este processo de leitura que se torna possível observar a atuação do componente de Flexibilidade Cognitiva, para que a leitura das palavras respeite o som de cada letra (Duarte et al, 2008;Medina et al, 2017).…”
Section: ) Avaliação Das Funções Executivasunclassified